DEVELOPMENT OF TOURISM IN UZBEKISTAN - Bozorboyeva Marjona; Munojat Isakdjanova (European Science Publishing, 2024)
This article examines the history and development of the tourism industry in Uzbekistan since the country gained independence in 1991. It analyzes key factors that have contributed to tourism growth, including government initiatives, infrastructure development, and marketing efforts. The article draws upon academic literature, government reports, and tourism statistics. Findings indicate that international tourist arrivals to Uzbekistan have increased significantly since the 1990s, with the greatest growth occurring in the last decade. The government has played an active role in promoting tourism through visa liberalization, tourism-friendly policies, and investment in transportation and hotel infrastructure. Private sector development and marketing campaigns have also been crucial.
Keywords: Uzbekistan, tourism development, tourism policy, silk road, Central Asia.